Optimalisasi pemasaran produk UMKM di Kelurahan Jambidan melalui pemanfataan WA Bisnis - Yulinda Erlistyarini; Wiwid Adiyanto; Novita Ika Purnamasari; Kadek Kiki Astria; Riski Damastuti; Alvian Alrasid Ajibulloh; Rr. Pramesthi Ratnaningtyas; Andreas Tri Pamungkas (Nur Science Institute, 2026)
Jambidan Village, Banguntapan Subdistrict, Bantul, Special Region of Yogyakarta (DIY), has potential for MSMEs and freshwater fish farming. Jambidan Village has the potential to become a tourist village developed by its community, rather than by a single business. The problems in the tourism village industry are the limited reach of product promotions, promotional packaging, and the use of promotional tools that can still be optimised. The purpose of this community service activity is to expand users' knowledge and skills in using WhatsApp Business as a business platform, which functions not only as a messaging application but also as a marketing tool to support promotional activities and increase sales. The results of this activity survey indicate an increase in knowledge and mastery in operating WhatsApp Business among MSMEs in Jambidan Village. Participants were also equipped with knowledge of basic product photography techniques and product packaging design to support the use of WhatsApp Business. The program for utilising digital media for promotional purposes requires continuity from its users. In addition, ongoing mentoring from practitioners and academics in digital marketing communications is needed.